(3OjhGf GHf GdfMGSs - (3aJM Gddg Hf YHO Gddg GdMdHj, GHf GdfMGS,J (B1052 (3g` s ((3YHO Gddg HGYaja s)
(3ChdgG (B:s
(3JPcQ GdSaM aGfgdJ ShGaMI hdjS jNaGc eG JNai LhGfMI UOY Gdghi jG YOhdi ZjQ edJje s
(3BNQgG (B:s
(3dc GdeYGdi hYdi GdaVd VeGf GdOQc s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B612s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs